A Semiotic Meaning Analysis of the Tradition “Famazawa Ono Alawe Nihalö” in a Traditional Wedding Ceremony in Afulu, North Nias (International Journal of Education and Literature, 2025)
This study aims to analyze the semiotic meanings and symbols used in the tradition of “Famazawa Ono Alawe Nihalö” in the traditional wedding ceremony of the Nias community in Afulu, North Nias. The method used in this research is descriptive qualitative with a semiotic approach by Charles Sanders Peirce, which views signs as representamen, object, and interpretation. Data collection techniques included literature review, field observation, and interviews with local figures from Afulu, North Nias. The data consisted of words, sentences, images, texts, and dialogues. The primary data sources were journals and an interview a cultural expert from Nias. The results of this study reveal that the symbols in the “Famazawa Ono Alawe Nihalö” tradition carry semiotic meanings that reflect respect for women, the sanctity of marriage, and the sociocultural structure of Nias society.